In vivo characterization of the bacterial intramembrane-cleaving protease RseP using the heme binding tag-based assay iCliPSpy - Kupke, Thomas; Götz, Rabea; Richter, Florian M.; Beck, Rainer; Lolicato, Fabio; Nickel, Walter; Hopf, Carsten; Brügger, Britta (Communications biology, 2023)
Regulated intramembrane proteolysis (RIP) describes the protease-dependent cleavage of transmembrane proteins within the hydrophobic core of cellular membranes. Intramembrane-cleaving proteases (I-CliPs) that catalyze these reactions are found in all kingdoms of life and are involved in a wide range of cellular processes, including signaling and protein homeostasis. I-CLiPs are multispanning membrane proteins and represent challenging targets in structural and enzyme biology. Here we introduce iCLiPSpy, a simple assay to study I-CLiPs in vivo. To allow easy detection of enzyme activity, we developed a heme-binding reporter based on TNFα that changes color after I-CLiP-mediated proteolysis. Co-expression of the protease and reporter in Escherichia coli (E. coli) results in white or green colonies, depending on the activity of the protease. As a proof of concept, we use this assay to study the bacterial intramembrane-cleaving zinc metalloprotease RseP in vivo. iCLiPSpy expands the methodological repertoire for identifying residues important for substrate binding or activity of I-CLiPs and can in principle be adapted to a screening assay for the identification of inhibitors or activators of I-CLiPs, which is of great interest for proteases being explored as biomedical targets.